Bronchial Artery Pseudoaneurysm as an Unsuspected Cause of Hemoptysis in a Pediatric Patient. (August 2014) - Patel, Rusha; Uchida, Derek; Feola, G. Peter; Meier, Jeremy D.
Objective: Hemoptysis in the pediatric population may be caused by foreign body aspiration, cystic fibrosis, bronchiectasis, or infection. Vascular causes are uncommon. We present a rare cause of hemoptysis related to a bronchial artery pseudoaneurysm. Methods: We report the case of a child with a bronchial artery pseudoaneurysm causing hemoptysis and describe the clinical evaluation, treatment, and outcome. Results: A 12-year-old girl presented to a tertiary children's hospital with a history of daily, intermittent, moderate-volume hemoptysis. Rigid bronchoscopy showed a fresh clot occluding the right bronchus intermedius. Computed tomography angiogram was concerning for mild external vascular compression of the right mainstem bronchus. A bronchial arteriogram showed a right mid-bronchial pseudoaneurysm, which was embolized without complication. On repeat bronchoscopy, thrombus was removed from the bronchus intermedius with no new active bleeding. The patient was discharged in stable condition and did not have any more episodes of hemoptysis. Additional medical work-up did not reveal another source of the patient's bleeding. Conclusion: Hemoptysis in the pediatric population can be inflammatory, infectious, or due to systemic disease. Although extremely rare, bronchial artery pseudoaneurysm should be considered in cases of moderate to severe intermittent hemoptysis without another identifiable cause. Bronchial angiography can be both diagnostic and therapeutic.